2011
DOI: 10.1111/j.1471-4159.2011.07256.x
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptor stimulation by dehydroepiandrosterone ameliorates cognitive impairment through activation of CaM kinase II, protein kinase C and extracellular signal-regulated kinase in olfactory bulbectomized mice

Abstract: Sigma-1 receptor (sigma-1R) was cloned in human and several animal species (Hanner et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 83 publications
3
43
0
Order By: Relevance
“…In this study, DHEA treatment caused a significant up-regulation of the p-CREB protein level in cultured rat primary Leydig cells. This result was consistent with Moriguchi et al [27], who reported that DHEA significantly restored the reduced ERK phosphorylation concomitant with increased CREB phosphorylation in hippocampal ca1. Saxena et al [52] reported that DHEA regulates the MAPK pathway in humans via a novel MAPK phosphatase, which not only controls the activity of MAPKs, but also mediates crosstalk between the cAMP system and the MAPK cascade.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, DHEA treatment caused a significant up-regulation of the p-CREB protein level in cultured rat primary Leydig cells. This result was consistent with Moriguchi et al [27], who reported that DHEA significantly restored the reduced ERK phosphorylation concomitant with increased CREB phosphorylation in hippocampal ca1. Saxena et al [52] reported that DHEA regulates the MAPK pathway in humans via a novel MAPK phosphatase, which not only controls the activity of MAPKs, but also mediates crosstalk between the cAMP system and the MAPK cascade.…”
Section: Discussionsupporting
confidence: 92%
“…Additional studies suggested that DHEA affects the phosphorylation/activation of ERKs by enhancing phosphorylation of the steroidogenic factor-1 (SF-1) and regulating the protein expression of steroidogenic enzymes. Moriguchi et al [27] reported that DHEA restored reduced ERK phosphorylation concomitant with increased CREB phosphorylation in the hippocampal ca1 region of olfactory bulbectomized mouse. Nevertheless, the molecular mechanisms underlying these DHEA effects in Leydig cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Memory-Related Behavioral Tasks (1) Y-maze task: The Ymaze task is described elsewhere [7]. Spontaneous alternation behavior in a Y-maze is assessed as an indicator of spatial reference memory.…”
Section: Methodsmentioning
confidence: 99%
“…Knockout mice lacking Sig-1R exhibit depressive-like behaviors [6]. We also recently reported that impaired cognitive-related and depressive-like behaviors in olfactory bulbectomized mice are improved by chronic oral administration of dehydroepiandrosterone (DHEA), an endogenous Sig-1R ligand [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…ST101 promotes nicotine-induced acetylcholine (ACh) release in the hippocampus via enhancement of Cav3.1 T-type calcium channel activity [18,19]. Recently, we developed a novel spiroimidazopyridine derivative called SAK3 (ethyl-8'-m e t h y l -2 ' , 4 -d i o x o -2 -[ p i p e r i d i n -1 -y l ] -2 ' Hspiro[cyclopentane-1, 3′-imidazo[1, 2-α]pyridin]-2-ene-3,carboxylate) that is a more effective T-type calcium channel enhancer than ST101 [20].…”
Section: Introductionmentioning
confidence: 99%